JOURNAL REVIEW: COLON CANCER SURVIVAL RATES WITH THE NEW AMERICAN JOINT COMMITTEE ON CANCER SIXTH EDITION STAGING - Bayu Aji Sismanto (CV. ADIBA AISHA AMIRA, 2025)
Colorectal cancer is one of the leading causes of cancer-related deaths worldwide, with a steadily increasing prevalence. According to data from the American Cancer Society, it is estimated that over 104,000 new cases of colorectal cancer will be diagnosed in the United States in 2021. Determining the stage of colorectal cancer is crucial in determining prognosis and appropriate treatment strategies, particularly the impact of the latest staging system on patient survival rates. This study employs a retrospective design, analyzing data from the national cancer registry, which includes patients diagnosed with colorectal cancer between 2000 and 2010. The sample population consisted of 10,000 patients who met inclusion criteria, including age, gender, and cancer stage at diagnosis. Data were collected from medical records and cancer registries, as well as other demographic and clinical information. Statistical analysis methods included Kaplan-Meier analysis to calculate five-year survival rates, and Cox regression models to evaluate risk factors influencing survival. The results will provide insights into the efficiency of the sixth edition of the AJCC staging system in predicting patient survival. The analysis revealed that the five-year survival rate for patients with stage I colorectal cancer reached 90%, while for stage IV it was approximately 10%. The study also found that factors such as age, gender, and the presence of comorbidities significantly influenced patient survival. The use of adjuvant therapy in stage III patients showed an increase in survival rates up to 70%. The sixth edition of the AJCC staging system makes a significant contribution to improving understanding of colorectal cancer patient survival. By using this system, doctors can identify high-risk patients and plan more effective interventions. Further research is needed to explore other factors that may influence survival, including the role of genetics and lifestyle. These findings are expected to serve as a foundation for developing better treatment strategies in the future.